2014
DOI: 10.1111/cei.12216
|View full text |Cite
|
Sign up to set email alerts
|

CD3ζ-based chimeric antigen receptors mediate T cell activation viacis- andtrans-signalling mechanisms: implications for optimization of receptor structure for adoptive cell therapy

Abstract: Chimeric antigen receptors (CARs) can mediate redirected lysis of tumour cells in a major histocompatibility complex (MHC)-independent manner, thereby enabling autologous adoptive T cell therapy for a variety of malignant neoplasms. Currently, most CARs incorporate the T cell receptor (TCR) CD3ζ signalling chain; however, the precise mechanisms responsible for CAR-mediated T cell activation are unclear. In this study, we used a series of immunoreceptor tyrosine-based activation motif (ITAM)-mutant and transmem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 33 publications
2
52
1
Order By: Relevance
“…26 Consistent with the reported physical incorporation of CAR elements into the endogenous TCR/CD3 complex, 35,36 we found that TCR-stimulated CAR.GD2 NKT cells exhibited a pattern of Th2-or Th1-like polarization that was nearly identical to that elicited by CAR stimulation and was again dependent on the presence of CD28 or 4-1BB endodomains in the CAR constructs (supplemental Figure 2).…”
Section: Cd28 and 4-1bb Car Endodomains Have Differential Effect On Nsupporting
confidence: 85%
“…26 Consistent with the reported physical incorporation of CAR elements into the endogenous TCR/CD3 complex, 35,36 we found that TCR-stimulated CAR.GD2 NKT cells exhibited a pattern of Th2-or Th1-like polarization that was nearly identical to that elicited by CAR stimulation and was again dependent on the presence of CD28 or 4-1BB endodomains in the CAR constructs (supplemental Figure 2).…”
Section: Cd28 and 4-1bb Car Endodomains Have Differential Effect On Nsupporting
confidence: 85%
“…For example, in a murine model, Yang et al [8] showed that TCR engagement negatively affected CD8+ CAR T-cell expansion. Similarly, Bridgeman et al [9] demonstrated that the interaction between TCR and CAR decreased CAR T-cell potential to eradicate tumor cells.…”
Section: Introductionmentioning
confidence: 95%
“…1 The CD19 antigen recognition domain is responsible for binding of the CAR T cell to CD19. CD3-z is critical for initiating T-cell activation and antitumor activity, as measured by cytotoxicity and cytokine production, 2 and the 4-1BB co-stimulatory signaling enhances proliferation, antitumor activity, oxidative metabolism, central memory differentiation, and persistence of the CTL019 cells both ex vivo and in animal models. 1,3,4 Early results from clinical studies of CTL019 in patients with CD19…”
Section: Introductionmentioning
confidence: 99%